2017
DOI: 10.7860/jcdr/2017/27385.10259
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Health Education using Facebook to Promote Healthy Lifestyle among Medical Students in Puducherry, India: A Non-Randomized Controlled Trial

Abstract: Except for the decrease in junk food intake, use of Facebook as an effective tool to promote healthy lifestyle could not be proved with confidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(47 citation statements)
references
References 9 publications
0
45
0
2
Order By: Relevance
“…With regards to design, 4 studies were randomised control trials (RCTs) [ 26 29 ], 3 mixed methods [ 30 32 ], 3 non-controlled before-after trials (NCBA) [ 33 35 ], 5 controlled before-and-after trial (CBA) [ 36 40 ], and 3 cross-sectional [ 37 , 39 , 41 ]. Most of the papers were published between 2017 and 2020 (13 of 16) [ 26 35 , 37 , 40 , 41 ], and included the following social media platforms: Facebook, Instagram, Reddit, Twitter, and WeChat. Most data were collected within the USA (9 studies) [ 28 30 , 33 37 , 39 ], and 11 out of 18 studies targeted young adults aged between 18 and 35 years old [ 26 , 28 , 29 , 33 , 36 40 ] and eight included college/university students [ 28 , 33 , 36 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…With regards to design, 4 studies were randomised control trials (RCTs) [ 26 29 ], 3 mixed methods [ 30 32 ], 3 non-controlled before-after trials (NCBA) [ 33 35 ], 5 controlled before-and-after trial (CBA) [ 36 40 ], and 3 cross-sectional [ 37 , 39 , 41 ]. Most of the papers were published between 2017 and 2020 (13 of 16) [ 26 35 , 37 , 40 , 41 ], and included the following social media platforms: Facebook, Instagram, Reddit, Twitter, and WeChat. Most data were collected within the USA (9 studies) [ 28 30 , 33 37 , 39 ], and 11 out of 18 studies targeted young adults aged between 18 and 35 years old [ 26 , 28 , 29 , 33 , 36 40 ] and eight included college/university students [ 28 , 33 , 36 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Most of the papers were published between 2017 and 2020 (13 of 16) [ 26 35 , 37 , 40 , 41 ], and included the following social media platforms: Facebook, Instagram, Reddit, Twitter, and WeChat. Most data were collected within the USA (9 studies) [ 28 30 , 33 37 , 39 ], and 11 out of 18 studies targeted young adults aged between 18 and 35 years old [ 26 , 28 , 29 , 33 , 36 40 ] and eight included college/university students [ 28 , 33 , 36 40 ]. Five of the 18 studies targeted specific populations including primigravid women [ 34 ], adults at risk of colorectal cancer [ 30 ], nurses [ 32 ], and overweight or obese individuals [ 27 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increase in physical activity was also noted where there was increase in the proportion of participants who traveled in the intervention group but not statistically significant, and similar results were seen in a study conducted by Krishnamohan et al where physical activity during travel was found to be increased in both groups but not statistically significant which might be due to smaller sample sizes. [ 11 ]…”
Section: Discussionmentioning
confidence: 99%
“…La mayoría de los estudios que se han realizado sobre la incorporación de las tecnologías digitales, pone en relieve que los avances de la tecnología en los diversos niveles educativos, mejoran y potencian la educación y la enseñanza (Krishnamohan et al, 2017). Algunos de ellos como los de Lampe et al aportan información acerca del uso de redes sociales como Facebook.…”
Section: Introductionunclassified